2018
DOI: 10.1016/j.ecocom.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined effect of matrix quality and spatial heterogeneity on biodiversity decline

Abstract: The land-sparing/land-sharing debate remains an oversimplified framework to evaluate landscape management strategies that aim to reconcile food production and biodiversity conservation. Still, biodiversity-yield curves, on which the framework has relied, provide valuable qualitative information on biodiversity's sensitivity to agricultural practices, and much research has studied this relationship. But the potential effect of

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…On the other hand, route of abiotic influence explained over 41% (Table 2). Although effects of dispersal on HDRs were weak compared to the effect of abiotic influence, we found that universal dispersal did reduce average species loss compared to the null model for routes 1 and 2 across all measured spatial scales (Figure 6 and Supplementary Figure 6), supporting the prediction that dispersal can mitigate local losses (Liao et al, 2013(Liao et al, , 2016Ramos et al, 2018). However, we found that when there was an interaction between routes 1 and 2, universal dispersal had the opposite effect and instead increased average species loss compared to the null model across sampling scales, (orange bars in Figure 6A and Supplementary Figure 6A), which occurred because uncorrelated effects of route 1 and 2 that led to more species when dispersal was adjacent led to no net change or fewer species when dispersal was universal (beige bars in Figure 6B and Supplementary Figure 6B).…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, route of abiotic influence explained over 41% (Table 2). Although effects of dispersal on HDRs were weak compared to the effect of abiotic influence, we found that universal dispersal did reduce average species loss compared to the null model for routes 1 and 2 across all measured spatial scales (Figure 6 and Supplementary Figure 6), supporting the prediction that dispersal can mitigate local losses (Liao et al, 2013(Liao et al, , 2016Ramos et al, 2018). However, we found that when there was an interaction between routes 1 and 2, universal dispersal had the opposite effect and instead increased average species loss compared to the null model across sampling scales, (orange bars in Figure 6A and Supplementary Figure 6A), which occurred because uncorrelated effects of route 1 and 2 that led to more species when dispersal was adjacent led to no net change or fewer species when dispersal was universal (beige bars in Figure 6B and Supplementary Figure 6B).…”
Section: Discussionsupporting
confidence: 74%
“…Agroecosystems cover around 40 % of the Earth’s surface (Foley et al 2005), represent a substantial part of the world’s biodiversity, and have just recently begun to be analyzed from a network perspective (Bohan et al 2013; López Martínez 2017). The insights gained from such a system-level approach hold the potential to guide our actions around major issues like autonomous pest control, disease outbreaks and biodiversity conservation in agricultural landscapes (Vandermeer et al 2010, 2018; Ramos et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Agroecosystems cover around 40 % of the Earth's surface (Foley et al 2005), represent a substantial part of the world's biodiversity, and have just recently begun to be analyzed from a network perspective (Bohan et al 2013;López Martínez 2017). The insights gained from such a system-level approach hold the potential to guide our actions around major issues like autonomous pest control, disease outbreaks and biodiversity conservation in agricultural landscapes (Vandermeer et al 2010(Vandermeer et al , 2018Ramos et al 2018).…”
Section: Introductionmentioning
confidence: 99%